RESOURCES COMPOSITION OF FISH RESULTS ABOUT TRACKING FISH IN WEST PAPUA MALAUMKARTA WATERS - poltak, hendra; Sururi, Misbah; Suruwaky, Amir Machmud; Katili, Vicky Rizky; Tjarles, Lay; Ismail, ismail (Jurnal Harpodon Borneo, 2022)
Hand line is a fishing gear consisting of a single string and hook for fishing and is widely used by fishermen in Malaumkarta waters. The purpose of this study is to identify the types of fish resources caught in the waters of Malaumkarta with the Drift Fishing system for resource conservation. The research was conducted 6 (six) times in 3 locations from June to September 2021. The method used was fishing survey using Handline Metal Jig drift system at depths 50 meters and 50 meters. The analysis was carried out quantitatively and qualitatively. The results showed that there were 134 individuals and 20 types of fish caught with a total weight of 126,194 kg. The type of fish that was most often caught was Letrinus sp, while in quantity it was Eumegistus illustris. The catch at three fishing locations showed that at a depth of 50 meters, 17 species were caught, 62 individuals, 104.625 kg with an average weight of 1.69 kg, while at a depth of 50 meters, 11 species were caught, 73 individuals, 22,039 kg with a weight of fish average 301.91 gr. The result of the research is that fish resources are utilized at a depth of 50 meters using a drift fishing system, with a metal jig fishing line.